Vantagens adicionais em híbridos de tomateiro do tipo Saladete provenientes de parental masculino anão - Pereira, Lucas Medeiros (2023)
The tomato plant has tremendous economic, social and nutritional importance. Among the various types of tomatoes, the Saladette /Italian segment stands out with its suitability for both fresh consumption and industrial processing. Production of this vegetable requires substantial investments per hectare. Strategies that increase productivity to offset these costs are fundamental. One proposal to increase productivity is the breeding of hybrids from dwarf parents to produce additional improvements in the Saladette-type tomato. This study aimed to evaluate possible improvements in agronomic performance and fruit quality of Saladette hybrids obtained from crosses between normal and dwarf strains. Seventeen tomato hybrids obtained from three backcrosses (BC1, BC2, and BC3) and two commercial control (cv. Bento and Vivacy) were evaluated. The agronomic characterization was performed by evaluating eight variables and fruit quality was evaluated using six variables. The data were analyzed using the mean test, and the artificial neural networks (ANNs) technique was used to study the dissimilarity among the hybrids. The hybrids obtained from the dwarf male parent exhibited morphological changes in the plants, including a reduction of internodes, a greater number of bunches per linear meter of plant, and biofortification of the fruits. There are indications that in the second backcrossing, it is already possible to produce potential dwarf parents to obtain hybrids.